Amphiphilic dendritic copolymers of tert‐butyl‐glycidylether and glycidol as a nanocontainer for an anticancer ruthenium complex. Issue 24 (8th October 2014) - Libera, Marcin; Formanek, Petr; Schellkopf, Leonard; Trzebicka, Barbara; Dworak, Andrzej; Stamm, Manfred
ABSTRACT Dendritic copolymers comprising a hydrophobic core and hydrophilic shell with nearly equal numbers of hydroxyl groups in the shell and different densities in the core were prepared by a multi‐step process based on anionic ring‐opening polymerization. The diversity in the core density was obtained by using copolymer stars with poly(tert‐butyl‐glycidylether)‐block‐polyglycidol arms with nearly equal length of hydrophobic blocks and numbers of hydroxyl groups of polyglycidol but different numbers of arms as macroinitiators. The ability of the dendritic copolymers to serve as a nanocontainer for a ruthenium complex Ru(NH3)3Cl3 with anticancer properties was studied. The possibility of improving the water solubility of this poorly soluble drug by loading it onto dendritic copolymers was investigated. The hydroxyl groups of the dendritic copolymers were used for complexation of the ruthenium compound to the shell. The loading efficiency was analyzed by UV–vis spectroscopy. The dendritic nanoparticles in their hydrated state were visualized using cryo‐TEM. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3488–3497